2008
DOI: 10.2139/ssrn.1261856
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of Olympic Games: Evidence from Stock Markets

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 6 publications
0
13
1
Order By: Relevance
“…These non-economic events had no economic effect on the stocks themselves, but were able to impact on investor mood. Research has addressed the relationship between stock market returns and various non-economic events, such as the weather (Saunders, 1993;Trombley, 1997;Zhu, 2006;Gerlach, 2007;Jacobsen & Marquering, 2008;Saporoschenko, 2011), sleep patterns (Kamstra, Kramers & Levi, 2000), seasonal affective disorder (Molin, Mellenrup, Bolwig, Scheike & Dam, 1996;Dolvin, Pyles & Wu, 2009), and mega sporting events (Berman, Brooks & Davidson, 2000;Matheson & Baade, 2004;Veraros, Kasimati & Dawson, 2004;Dick & Wang, 2010;Floros, 2010;Mirman & Sharma, 2010). If non-economic events are able to affect an individual's mood and hence influence market prices, it can be deduced that sporting performance is able to influence both investor mood and market prices.…”
Section: Stock Markets and Sporting Performancementioning
confidence: 99%
“…These non-economic events had no economic effect on the stocks themselves, but were able to impact on investor mood. Research has addressed the relationship between stock market returns and various non-economic events, such as the weather (Saunders, 1993;Trombley, 1997;Zhu, 2006;Gerlach, 2007;Jacobsen & Marquering, 2008;Saporoschenko, 2011), sleep patterns (Kamstra, Kramers & Levi, 2000), seasonal affective disorder (Molin, Mellenrup, Bolwig, Scheike & Dam, 1996;Dolvin, Pyles & Wu, 2009), and mega sporting events (Berman, Brooks & Davidson, 2000;Matheson & Baade, 2004;Veraros, Kasimati & Dawson, 2004;Dick & Wang, 2010;Floros, 2010;Mirman & Sharma, 2010). If non-economic events are able to affect an individual's mood and hence influence market prices, it can be deduced that sporting performance is able to influence both investor mood and market prices.…”
Section: Stock Markets and Sporting Performancementioning
confidence: 99%
“…About the correlation between host country and stock return, there some studies explaining the different result. The summer games represent a larger event and then more likely to have a significant impact [5]. The another result showed well performance of stock market for the Greece regarding the Summer Olympic Games, South Korea regarding the 2002 FIFA World Cup, Portugal regarding the 2004 European Football Championships and United States regarding 1996 Summer Olympic Games.…”
Section: Introductionmentioning
confidence: 86%
“…Chen et al (2007) results showed that the outbreak of the SARS epidemic after the Taiwan hotel stock price compensation had a significantly negative impact on hotel stock price returns in Taiwan. Dick and Wang (2010) used the event study method to examine the impact of announcements made by the International Olympic Committee (IOC) as to which cities would host the games on the major stock index returns of the winning and losing countries. Data covering the period 1988 -2014 in relation to 15 announcements as to which countries would host future Olympic Games were used in the event study.…”
Section: Identifying the Cross-strait Events In 2014-2016mentioning
confidence: 99%